2024 Global report on food crises: Joint analysis for better decisions - Food Security Information Network; Minot, Nicholas; Rice, Brendan; Vos, Rob (Food Security Information Network, 2024)
The Global Report on Food Crises (GRFC) 2024 confirms the enormity of the challenge of achieving the goal of ending hunger by 2030. In 2023, nearly 282 million people or 21.5 percent of the analysed population in 59 countries/territories faced high levels of acute food insecurity requiring urgent food and livelihood assistance. This additional 24 million people since 2022 is explained by expanded analysis coverage as well as deteriorating acute food insecurity in some countries outweighing improvements in others. Palestine (Gaza Strip) and the Sudan were the most devastatingly deteriorating food crises. The number of people experiencing catastrophic levels of acute food insecurity rose to over 0.7 million – almost double the number of 2022 – with nearly 0.6 million of them in the Gaza Strip.